2017
DOI: 10.1002/ecy.1658
|View full text |Cite
|
Sign up to set email alerts
|

Termites promote resistance of decomposition to spatiotemporal variability in rainfall

Abstract: The ecological impact of rapid environmental change will depend on the resistance of key ecosystems processes, which may be promoted by species that exert strong control over local environmental conditions. Recent theoretical work suggests that macrodetritivores increase the resistance of African savanna ecosystems to changing climatic conditions, but experimental evidence is lacking. We examined the effect of large fungus-growing termites and other non-fungus-growing macrodetritivores on decomposition rates e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 47 publications
6
43
1
Order By: Relevance
“…It seems the decomposition rates associated with active Macrotermes mounds are not dependent on moisture, consistent with Veldhuis et al. (). On a larger scale, Leitner et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It seems the decomposition rates associated with active Macrotermes mounds are not dependent on moisture, consistent with Veldhuis et al. (). On a larger scale, Leitner et al.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study from South Africa found that fungus‐growing termites ( Macrotermes ) maintained high levels of decomposition even when moisture was scarce thus decoupling decomposition rates from rainfall (Veldhuis et al. ). Mound‐building termites occur throughout the ~10 million square kilometer African savanna (Riggio et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased summer temperatures in the region will initiate more frequent freeze-thaw cycles in dry soils, increasing mortality of the dominant invertebrate (Knox et al 2016(Knox et al , 2017. Snow cover in the McMurdo Dry Valleys is patchy and ephemeral, and soils completely lack plant cover and ecosystem engineering macrofauna, thereby they are devoid of abiotic and biotic buffers that, in other ecosystems, can mitigate the impact of harsh atmospheric conditions (Pauli et al 2013, Andriuzzi et al 2015, Veldhuis et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As ecosystem engineers, termites are responsible for large-scale bioturbation, soil aeration, and organic matter decomposition, altering physical, chemical, and biological properties of soils, which in turn affect plant growth and diversity (Garba et al, 2011;Van der Plas et al, 2013;Jouquet et al, 2015). The decomposition of complex organic matter into nutrients available for plants is one of the most important ecosystem services termites provide to tropical forests, which leads to ecosystem stabilisation under global change (Obi & Ogunkunle, 2009;Bonachela et al, 2015;Veldhuis et al, 2017). Termites also increase net productivity of the system, and termite removal in crop fields leads to decreased quality and quantity of the harvest (Evans et al, 2011).…”
Section: Introductionmentioning
confidence: 99%